"We preserved everything old" - Prelić, Mladena (Traditiones (Ljubljana), 2012)
The paper discusses the conceptualization of two widely spread concepts of culture of ethnic minorities - one which implies that the minority culture is by definition a traditionalist one, and the other that implies it is based exclusively or predominantly on traditional folk culture. These concepts have an impact on the self-understanding of members of the minorities themselves, as well as on the policies toward them by the relevant circles of the majority society. The data used in the discussion is mostly obtained during the long-term field study of Serbs in Hungary.
Keywords: ethnology; Etnologija; Narodne manjšine; national minorities; folk culture; Ljudska kultura; ethnic identity; Narodna identiteta; Madžarska; Hungary; Serbs; Srbi